2010
DOI: 10.1177/1534735409359073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patterns, and Costs of Chinese Medicine Use Among Prostate Cancer Patients: A Population-Based Study in Taiwan

Abstract: Background. Taiwan's National Health Insurance (NHI) is a comprehensive and universal program, providing Western medicine (WM) and Chinese medicine (CM). This study aims to explore CM use among prostate cancer patients in NHI. Methods. A cross-section retrospective analysis was conducted using registration and claim data sets from the NHI Research Database. In 2007, 22 352 prostate cancer patients with 265 497 visits of CM and WM ambulatory services were identified. Patient demographics, patterns of therapies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
3
20
1
Order By: Relevance
“…This publicly available research database provides comprehensive data gathered under unrestricted access and is particularly valid for investigating TCM. A number of TCM studies have been published using this nationwide prescription database Chen et al, 2006Chen et al, , 2008aHsieh et al, 2008;Yang et al, 2009;Jong et al, 2010;Lin et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…This publicly available research database provides comprehensive data gathered under unrestricted access and is particularly valid for investigating TCM. A number of TCM studies have been published using this nationwide prescription database Chen et al, 2006Chen et al, , 2008aHsieh et al, 2008;Yang et al, 2009;Jong et al, 2010;Lin et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that Traditional Chinese Medicine (TCM) has effects on androgen-dependent and -independent prostate carcinoma (7)(8)(9). At present, there are seldom resources of TCM for the treatment of prostate carcinoma and the results of clinical and experimental studies are indispensable for further data regarding TCM therapy for the treatment of this disease (10).…”
Section: Introductionmentioning
confidence: 99%
“…9,18,22 The current authors' previous cross-sectional study found the most frequently used Chinese medicine therapies among patients with prostate cancer were Chinese herbal medication (93.6% as shown by visits), followed by acupuncture/ traumatology manipulative therapies (7.0% as shown by visits). 23 However, the prevalence of acupuncture was not available because of data limitation. In this study, the prevalence of acupuncture use was much higher, ranging from 7.5% to 8.6% in each cross-sectional year and, overall, was 14.6% during [2002][2003][2004][2005][2006][2007][2008].…”
Section: Discussionmentioning
confidence: 99%